The Influence of H2O2 on The Photocatalytic Pretreatment of Cellulose for 5-Hydroxymethyl Furfural (5-HMF) Production - Muhammad Imam Syafi’i; Khanin Nueangnoraj; Siwarutt Boonyarattanakalin (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Photocatalysis has been widely known as a simple green technology to be applied in the synthesis and degradation process of organic molecules. An application of photocatalysis in a biomass pretreatment for a 5-hydroxymethylfurfural (5-HMF) production was investigated in this study. The results have revealed that photocatalysis, applied during pretreatment, facilitates the breakdown of cellulose. The presence of oxidizing agent (H2O2) in the ratios to cellulose of 11:1, 18:1, and 37:1 mol.mol-1 has been investigated for its effect on the production of 5-HMF. The optimum conditions obtained for the pretreatment process was the presence of H2O2 at 37:1 mol.mol-1, which was followed by the process of evaporation of the remaining H2O2 after pretreatment. The 5-HMF yield from the hydrolysis process involving pretreatment was 13.07%, while the yield from the process without pretreatment was 9.79%. The application of the pretreatment has succeeded in increasing the 5-HMF yield by 25.09%. The progress in the pretreatment was also marked by the presence of the carboxyl groups in the pretreated samples which were observed by the Fourier Transforms Infrared spectroscopy (FTIR). Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).